Menguak Makna Laba Pedagang Sayur Keliling (Balijjah) Laki-Laki Dalam Perspektif Nilai Spritual - Auliyah, Robiatul; Angraini, Merie Satya (LP2M IAI Miftahul Ulum Pamekasan, 2024)
This study aims to uncover the awareness of the meaning of